Learning on the job and the cost of business cycles - Karl Walentin; Andreas Westermark (Sveriges Riksbank, 2018)
We show that business cycles reduce welfare through a decrease in the average level of employ- ment in a labor market search model with learning on-the-job and skill loss during unemployment. A negative correlation between unemployment and vacancies implies, via the concavity of the matching function, that business cycles reduce the average number of new jobs and employment. Learning on-the-job implies that the decrease in employment reduces aggregate human capital. This, in turn, reduces the incentives to post vacancies, further decreasing employment and human capital. We quantify this mechanism and .nd large output and welfare costs of business cycles.
Keywords: E32; J64; 330; Search and matching; labor market; human capital; stabilization policy; skill loss